Perceptions of Local Stakeholders on the Economic Impact of the Gaddachauki Open Border: A Descriptive Study of the Mahendranagar Market - Bhatt, Nisha; Bhatt, Deepak Raj (Brixton Scholarly Review, 2026)
Nepal Indian open border has been found to play a significant role in promoting economic activities in border markets, especially in markets such as Mahendranagar, which is close to the Gaddachauki border. While open borders are known to promote economic activities, their economic effects on border markets remain under-explored in literature. The main purpose of this study is to examine the perceptions of local stakeholders on the economic effects of the Gaddachauki open border on the Mahendranagar border market. While descriptive cross-sectional research design was used in this study, primary data were collected through a structured questionnaire administered to 150 respondents, with data being analyzed using descriptive statistics such as frequencies, percentages, and mean scores. The results indicate that stakeholders perceive the open border as beneficial in terms of access to goods and trade opportunities, at the same it poses challenges such as increased competition, pressure on local businesses, and financial instability for small business. A large proportion of respondents of the study expressed the need for restructuring the existing border trade system to enhance local market opportunities competitiveness. The study concludes that stakeholder perceives valuable offer insights for local-level economic planning and policy formulation, emphasizing the importance of balanced border management strategies in open-border economies.